2010
DOI: 10.1007/s00059-010-3244-3
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Disease in Pregnancies Complicated by Maternal Diabetes Mellitus

Abstract: This study shows an increased likelihood of specific heart anomalies, namely transposition of the great arteries, persistent truncus arteriosus, visceral heterotaxia and single ventricle, among offspring of diabetic mothers. This suggests a profound teratogenic effect at a very early stage in cardiogenesis. The study emphasizes the frequency with which the offspring of diabetes-complicated pregnancies suffer from complex forms of congenital heart disease. Pregnancies with poor 1st-trimester glycemic control ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(61 citation statements)
references
References 56 publications
1
54
1
5
Order By: Relevance
“…Bi-allelic loss of function mutations in PFKM result in diabetes as well as glycogen storage disease type VII (Tarui's disease) [62]. Our interest in PFKP was therefore additionally piqued by an unexplained, but longrecognized, increased risk for heterotaxy among the children of diabetic mothers [63].…”
Section: (B) Copy Number Variant Analyses Identify Novel Heterotaxy Gmentioning
confidence: 99%
“…Bi-allelic loss of function mutations in PFKM result in diabetes as well as glycogen storage disease type VII (Tarui's disease) [62]. Our interest in PFKP was therefore additionally piqued by an unexplained, but longrecognized, increased risk for heterotaxy among the children of diabetic mothers [63].…”
Section: (B) Copy Number Variant Analyses Identify Novel Heterotaxy Gmentioning
confidence: 99%
“…Hiperglisemi durumunda glikozdan sorbitol oluşumu artar. Bu madde, serbest oksijen radikallerinin artmasına yol açar, hücre ve DNA hasarı meydana gelir 10,13 . Gebelikte DM hastalığı tespit edildiğinde hastalığın başlama zamanı, süresi ve vasküler komplikasyonların varlığına göre White sınıflaması yapılır.…”
Section: Patofizyolojiunclassified
“…Başka bir çalışmada, DAB'ların % 13'ünde DKH bulunduğu tespit edilmiştir 23 . Spesifik hastalıklar arasında ventriküler septal defekt (VSD), atriyal septal defekt, atriyoventriküler septal defekt, VSD ile birlikte olabilen veya interventriküler septumun intakt olduğu büyük arter transpozisyonu (BAT), trunkus arteriyozus, çift çıkışlı sağ ventrikül, Fallot tetralojisi, triküspit, pulmoner ve mitral atrezi, patent duktus arteriyozus, tek atriyum, tek ventrikül, hipoplastik sol kalp sendromu, Ebstein anomalisi, pulmoner stenoz, aort stenozu, total veya parsiyel anormal pulmoner venöz dönüş, heterotaksi sendromları, aort koarktasyonu ve tek umblikal ven sayılabilir 8,10,13,15,19,24,25 . Patent duktus arteriyozus, doğumdan sonraki ilk 48 saatte normal bebeklere göre daha sık tespit edilir ama genelde kendiliğinden veya medikal tedavi ile kapanır, cerrahi ligasyona gerek kalmaz 10,16 .…”
Section: Doğumsal Kalp Hastalıklarıunclassified
“…Transposition of the great vessels, Fallot tetralogy, double outlet right ventricle, persistent truncus arteriosus, and aortic arch interruption are included in this category. A review of the literature by Lisowski et al has shown that these defects make up about a quarter of heart disease found in children of diabetic mothers [5]. The pathological process underlying this altered morphogenesis is not entirely clear.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, incidence of congenital heart disease is increased by about 4 times compared to the general population [1]. Conotruncal malformations are the most frequent cardiac alterations [4,5]. This group of congenital defects affects ventricular outflows and large arteries and originate from an interruption in the process of septation and rotation of common arterial trunk from which normally the aorta and the pulmonary artery separate.…”
Section: Introductionmentioning
confidence: 99%